An Item Response Theory analysis of the Unified Multiple System Atrophy Rating Scale. (January 2022) - Foubert-Samier, Alexandra; Pavy-Le Traon, Anne; Saulnier, Tiphaine; Le-Goff, Mélanie; Fabbri, Margherita; Helmer, Catherine; Rascol, Olivier; Proust-Lima, Cécile; Meissner, Wassilios G.
Abstract: Introduction: The Unified Multiple System Atrophy Rating Scale (UMSARS) has four subscales that have been specifically designed for the clinical assessment of MSA patients. UMSARS I (activities of daily living) and II (motor examination) subscales are regularly used as primary endpoints in treatment trials. The main objective of this study was to identify UMSARS I and II subscale items that best describe progression over time. Methods: All MSA patients seen at the French Reference Centre for MSA from 2007 to 2020 were included in a prospective cohort with an annual follow-up assessment including UMSARS. The repeated measures of the 26 UMSARS I and II items were analyzed using a longitudinal Item Response Theory model to identify the most informative items for each of the five UMSARS IV disease stages. Sample size estimates were further calculated for the most informative items as a group. Results: A total of 557 MSA patients were included with a mean follow-up of 2.3 years. The majority of items progressed with disease duration or across the different UMSARS IV disability stages, with the exception of those related to dysautonomia. Roughly 70% of the scale information was carried by only 11/26 items, many reflecting the patient perspective. These yielded similar sample size estimates than UMSARS I + II items. Conclusion: This study provides important information about the progression of UMSARS I and II subscale items. Improvements seem particularly necessary regarding those assessing dysautonomia. A shortened scale may be useful as outcome for future clinical trials. Highlights: The majority of UMSARS item scores progressed with disease duration and disability. 70% of the scale information was carried by only 11/26 items. These 11 items reflect patient-centered outcomes. A shortened scale based on these items may be useful for future clinical trials. Improvements seem necessary regarding items assessing dysautonomia.